A critical review of Malawi’s Special Crops Act and Agriculture (General Purposes) Act - Comstock, Andrew R.; Benson, Todd; Nankhuni, Flora; Kanyamuka, Joseph; Nyirenda, Zephania; Nyondo, Christone (International Food Policy Research Institute, 2019)
This report is a critical review of two of the principal agricultural laws in Malawi, the Special Crops Act and the Agriculture (General Purposes) Act. Both are frequently used to justify interventions by government in agricultural marketing and trade activities. The review is to assess whether this legislation is effective in promoting the goals of the country around agricultural commercialization, and if not, to provide recommendations for revisions to the laws. As a secondary task, the review considers whether either law could be used as an appropriate legal framework for contract farming regulation and oversight. The review was based on a thorough desk review of the legislation and interviews with over 230 key informants involved in agricultural production, marketing, and trade. The interviews focused on the laws and how their application by government has affected the commercial activities of the informants for better or for worse.